Women and formal vocational education and training in Zambia - Kane, Eileen [Verfasser] (International Labour Office, 1990)
"This report was commissioned by the International Labour Organisation and funded by the Development Cooperation Division of the Irish Department of Foreign Affairs. The field research was carried out in a three week period, December 1987 - January 1988. One of the functions of vocational education and training is to enhance people's ability to participate in the economy. Chapter I of the study looks at relevant aspects of the economy in Zambia whereas chapter II focusses on the role of women in the Zambian economy. The role of education generally, and of vocational education in particular, in women's economic lives is described in chapters III and IV. Chapter V and VI attempt to explain some of the factors affecting women's participation in vocational education." (Excerpt, BIBB-Doku)
Keywords: G 1.2 Arbeitsmarkt; G 2.4.5 Gender Mainstreaming; S 4.3.5 Bildungsbeteiligung & soziale Gerechtigkeit; I 2.3.1 Afrika; P 1.3 Frauen; Arbeitsmarkt; Bildungssystem; Sambia; Frauen; Frauenbildung; Bildungsniveau; Geschlechterrolle; Bildungschancengleichheit